Magnetic Nanomaterials for Hyperthermia-Based Therapy, Imaging, and Drug Delivery - Constantin Mihai Lucaciu (Pharmaceutics, 2024)
In recent years, nanomedicine has experienced remarkable advancements, due to the development of new nanomaterials with outstanding properties that have demonstrated significant advantages over traditional medicines [...]